A compreensão da terminologia legal e dos processos judiciais pelas crianças - Ana Sacau; Gloria Jólluskin; Teresa Toldy; Ana Oliveira; Joana Morais (e-cadernos ces)
Many European Directives point out the need to create child-friendly justice systems. These documents emphasize the need to adapt the language used to the age and understanding capacity of children involved in legal proceedings. Research in the area shows that the manner in which interviews are conducted has a strong impact on the quality of a child’s testimony. “The analysis of children's comprehension of legal terminology and court proceedings” is a project funded by FCT (Science and Technology Foundation) that aims to verify children's understanding of legal terminology used in Portuguese courts when they take statements from children. The project seeks to develop a tool that will enable magistrates to establish a better communication with children in this context.